Complete chloroplast genome sequences of Phlomis fruticosa and Phlomoides strigosa and comparative analysis of the genus Phlomis sensu lato (Lamiaceae) - Zhao, Wei; Guo, Lirong; Yang, Yu; Wang, Yan; Yang, Li; Wei, Cuimei; Guo, Jian; Yan, Kan; Chen, Haijuan; Yang, Zhigang; Li, Yimeng (Frontiers in Plant Science, 2022)
The taxonomic terms “Phlomis” and “Phlomoides” had been used to describe two sections within the genus Phlomis belonging to the Lamiaceae family. Recently, phylogenetic analyses using molecular markers showed that Phlomis and Phlomoides formed two monophyletic clades, and thus they are generally accepted as separate genera. In this study, we assembled the complete chloroplast genome of Phlomis fruticosa, which is the first reported chloroplast genome belonging to Phlomis genus, as well as the complete chloroplast genome of Phlomoides strigosa belonging to Phlomoides genus. The results showed that the length of chloroplast genome was 151,639 bp (Phlomis fruticosa) and 152,432 bp (Phlomoides strigosa), with conserved large single copy regions, small single copy regions, and inverted repeat regions. 121 genes in Phlomis fruticosa and 120 genes in Phlomoides strigosa were annotated. The chloroplast genomes of Phlomis fruticosa, Phlomoides strigosa, and three reported Phlomoides species, as well as those of 51 species from the Lamiaceae family, which covered 12 subfamilies, were subjected to phylogenetic analyses. The Phlomis and Phlomoides species were split into two groups, which were well supported by both maximum likelihood and Bayesian inference tree analyses. Our study provided further evidence to recognize Phlomis and Phlomoides as independent genera.